Public-Private Partnership Pembangunan Infrastruktur: Dilema Etik dan Praktik - Lutfah Ariana (Journal of Infrastructure Policy and Management (JIPM), 2024)
Over the past decade, Public-Private Partnership (PPP) has emerged as an alternative scheme for financing government infrastructure development. This scheme addresses the fiscal limitations that constrain infrastructure development funding. However, implementing PPP contracts and collaborating with the private sector continue to generate controversy, particularly regarding public concerns about privatization and misconceptions surrounding the scheme’s use. This article analyzes the challenges of PPP implementation from philosophical perspectives to understand how the government and private sector can effectively cooperate within the PPP framework. Using Popper’s falsification approach, the article argues that the PPP scheme cannot be universally applied to all projects as widely explained in most feasibility studies and cost-benefit analysis. The stakeholders involved in PPP projects operate within different dimensions of ontology and axiology. Therefore, this article examines the ethical framework necessary for the specific application of PPP schemes, tailored to the unique characteristics and principles of different projects and sectors.